Evaluasi Kontribusi Personal Selling, Strategi Iklan, dan Pelayanan terhadap Keputusan Konsumen untuk Membeli Handphone OPPO di Gerai Halup Cell - Abd Kadir; Irwansyah Irwansyah; Jemi Arafik; Feri Diansyah; Darmono Darmono; Muhammad Bayu; Djupiansyah Ganie; Yohanes Sri Guntur (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to analyze the effect of personal selling, advertising, and service quality on consumer buying interest in OPPO mobile phones at Halup Cell Store Berau. The research method uses a quantitative approach with a sample of 90 respondents. The results showed that personal selling and service quality had a significant partial effect on buying interest, while advertising did not. Simultaneously, all three variables significantly influenced consumer buying interest.